Productivity and Quality of Aromatic Rice (Oryza sativa L.) Varieties under Varying Level of Vermicompost - Patra, Partha Sarathi; Mondal, Prithusayak; Sarkar, Ashutosh; Choudhury, Ashok (International Journal of Bio-resource and Stress Management, 2023)
The present investigation was conducted during kharif seasons of 2018–19 and 2019–20 at the instructional farm of Uttar Banga Krishi Viswavidyalaya, Pundibari, Cooch Behar, West Bengal, India to evaluate the performance of aromatic rice varieties under varying level of vermicompost. The experiment was arranged out in split plot design where three aromatic rice varieties Kataribhog, Geetanjali and CR S. Dhan-910 were allocated in main plots and five level of nutrient management fitted in sub plots namely NM1: 100% RDF (60:30:30 kg NPK ha-1), NM2: Vermicompost @ 2 t ha-1, NM3: Vermicompost @ 3 t ha-1, NM4: Vermicompost @ 4 t ha-1 and NM5: Vermicompost @ 5 t ha-1 and replicated thrice. Results revealed that among the variety Geetanjali was found superior in terms of yield attributes and gave 5.32 and 15.73% yield advantage respectively over CR Dhan-910 and Kataribhog. Pooled data over the years revealed that variety Geetanjali recorded highest amount of carbohydrate (79.61%), starch (73.82%), amylose (24.19%) and lipid (2.63%) while highest protein (9.92%) was found in Kataribhog. Among the level of nutrient management 5 t ha-1 of vermicompost (NM5) ominously enhanced yield attributes, grain yield, grain quality as well as soil quality irrespective of variety and year of experimentation. Highest net return to the tune of ` 99212.80 and ` 82441.75 ha-1 and B:C ratio of 2.20 and 1.79 was realized with variety Geetanjali through 100% recommended dose of fertilizer.